MALToma with a ‘B’—Not for Benign, but for Bronchus-Associated: A Rare Case of Bronchus-Associated Lymphoid Tissue Lymphoma - Maneesh Gaddam MD; Dedeepya Gullapalli MD; Shyam Ganti MD; Sunil Badami MD; Kinnera Sahithi Urlapu MD (Journal of Investigative Medicine High Impact Case Reports)
Bronchus-associated lymphoid tissue (BALT) lymphoma is a rare subtype of extra-nodal marginal zone B-cell lymphomas, accounting for less than 5% of cases. It is typically indolent and often discovered incidentally through imaging studies performed for unrelated reasons. We present the case of a 72-year-old male with a known history of thoracic aortic dilatation, who was found to have a spiculated right upper lobe (RUL) pulmonary nodule on surveillance imaging. He remained asymptomatic, with no constitutional or respiratory symptoms. Positron emission tomography imaging demonstrated mildly increased uptake (standardized uptake value 2.4) of the RUL nodule, and no mediastinal or hilar lymphadenopathy. Bronchoscopic biopsy with histopathology and immunohistochemistry revealed a low-grade B-cell non-Hodgkin’s lymphoma, with CD20 and BCL2 positivity. Flow cytometry confirmed monoclonal B-cell proliferation, and fluorescence in situ hybridization analysis identified the BIRC3-MALT1 translocation, consistent with BALT lymphoma. The patient was staged as IE, and a decision was made for conservative management with active surveillance, given the localized and asymptomatic nature of his disease. While treatment options may include surgery, radiotherapy, immunotherapy, or chemotherapy, there is no consensus on the optimal approach due to the rarity and heterogeneous presentation of this lymphoma. In many early-stage cases without symptoms, a “watch and wait” strategy is reasonable. This case underscores the importance of including BALT lymphoma in the differential diagnosis of incidental pulmonary nodules and highlights the need for greater awareness and research to establish standardized treatment protocols, with each case adding valuable insight to guide future management strategies.